2021
DOI: 10.3389/fmars.2021.589242
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Reproductive Success of Western Baltic Herring (Clupea harengus) as a Response to Warming Winters

Abstract: Shallow estuaries, bays, and lagoons are generally considered hot spots of ocean productivity that often adjust rapidly to seasonal variations in atmospheric temperatures. During spring when biological reproductive processes begin in the temperate zones, regional climate variability can be immense and uncovering a non-linear biological response, such as fish recruitment to changing temperature regimes might be challenging. Using herring as a paradigm for a response of coastal spring productivity to regional cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…The 5 sub-regions identified in this study show significant differences in SST trends by season, which can lead to very different pressures on marine ecosystems. For instance, a recent study shows that the temperature threshold triggering initial spawning of herring in the southwestern Baltic Sea is 3.5-4.5 °C (Polte et al 2021). Their results revealed that the late seasonal onset of cold spells, the corresponding lengthening of the larval hatching period and early larval hatching peaks significantly reduced larval production and ultimately led to a reduced abundance of juveniles.…”
Section: Discussionmentioning
confidence: 99%
“…The 5 sub-regions identified in this study show significant differences in SST trends by season, which can lead to very different pressures on marine ecosystems. For instance, a recent study shows that the temperature threshold triggering initial spawning of herring in the southwestern Baltic Sea is 3.5-4.5 °C (Polte et al 2021). Their results revealed that the late seasonal onset of cold spells, the corresponding lengthening of the larval hatching period and early larval hatching peaks significantly reduced larval production and ultimately led to a reduced abundance of juveniles.…”
Section: Discussionmentioning
confidence: 99%
“…A low lipid content of the yolk may therefore increase larval mortality in the Baltic herring in warm springs if the consumption of energy increases, causing fast depletion of lipids in the egg yolk. The link between rising winter temperature and reduction of the herring's reproductive success has already been established in the southern Baltic Sea (Polte et al, 2021). In the northern Baltic, no respective findings have been made this far, but here, also salinity may contribute to the reproductive success of the species in addition to temperature as both show an effect on the females.…”
Section: Egg Qualitymentioning
confidence: 71%
“…All birds occupied shallow coastal waters, broadly overlapping with traditional herring Clupea harengus spring spawning sites in archipelagos and bays (Hede Jørgensen et al 2005a, b). The onset of the spawning season varies with water temperature, first spawning activities in the Archipelago Sea occur in late April in mild springs (Rajasilta et al 1993;Polte et al 2021). Spring stopovers in the Baltic Sea would thus probably match the early phase of Herring spawning in most years.…”
Section: Spring Migrationmentioning
confidence: 99%
“…Food intake during spring migration may affect the condition of the birds upon arrival at the breeding sites and thus the ability to produce eggs and incubate in time during the short Arctic spring. Warming water temperatures already impact timing and amount of herring reproduction in the Baltic (Polte et al 2021) and may affect the food resources in the White Sea as well. The possible impacts of such changes on the breeding performance of sea ducks will be important to study in future.…”
Section: Spring Migrationmentioning
confidence: 99%